Among Fortune’s Favored 500 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1966)
The 38 companies listed below are those substantially engaged in the mining of metals, non- metals, or coal which appeared among the country's top 500 (on the basis of sales volume) listed in the July 1966 issue of Fortune. General Motors, with $20.7 billion in sales, heads the entire list, and a prominent member of the mining industry, Island Creek Coal, occupies the 500th spot with sales of $109.6 million. The lists of "industry medians" following mining's "Top 38" reveal how well the mining industry fared in 1965 in various salient categories of business performance.